The relationship between siblings' college choices: Evidence from one million SAT-taking families. (October 2015) - Goodman, Joshua; Hurwitz, Michael; Smith, Jonathan; Fox, Julia
Abstract: Recent empirical work has demonstrated the importance both of educational peer effects and of various factors that affect college choices. We connect these literatures by highlighting a previously unstudied determinant of college choice, namely the college choice made by one's older sibling. Data on 1.6 million sibling pairs of SAT-takers reveals that younger and older siblings' choices are very closely related. One-fifth of younger siblings enroll in the same college as their older siblings. Compared to their high school classmates of similar academic skill and with observably similar families, younger siblings are about 15–20 percentage points more likely to enroll in 4-year colleges or highly competitive colleges if their older siblings do so first. These findings vary little by family characteristics. Younger siblings are more likely to follow the college choices of their older siblings the more they resemble each other in terms of academic skill, age and gender. We discuss channels through which older siblings' college choices might causally influence their younger siblings, noting that the facts documented here should prompt further research on the sharing of information and shaping of educational preferences within families. Highlights: Data on 1.6 million sibling pairs of SAT-takers reveals that younger and older siblings' choices are very closely related. One-fifth of younger siblings enroll in the same college as their older siblings. Controlling for rich covariates, younger siblings are 15–20 percentage points more likely to enroll in 4-year colleges or highly competitive colleges if their older siblings do so first. Younger siblings are more likely to follow the college choices of their older siblings the more they resemble each other in terms of academic skill, age and gender. These facts should prompt further research on the sharing of information and shaping of educational preferences within families.